Effect of process technology on the nutritional, functional, and physical quality of grapefruit powder. (January 2017) - Agudelo, C; Igual, M; Camacho, MM; Martínez-Navarrete, N
The health properties of fruit are widely known. Powdered fruit may be a practical format to be offered to the consumer. Nevertheless, the process used to obtain the powder must ensure the maximum retention of the bioactive compounds and the functional value of the fruit while retaining adequate physical properties. The aim of this study was to compare freeze-drying and spray drying as the drying technologies to obtain grapefruit powder. The obtained results allow freeze-drying to be proposed as a better technology than spray drying in order to obtain a product with a higher content of vitamin C and total carotenoids. Moreover, all of the edible part of the fruit is used in this case, so a greater quantity of healthy compounds is preserved and by-product generation is avoided. Adding about 6 g water, 4 g Arabic gum and 0.6 g bamboo fibre/100 g grapefruit pulp is recommended before freeze-drying.